Evaluation of Antimicrobial Activity and Molecular Docking of Artemisia herba-alba Growing in the Al-Muthanna Desert, Iraq - Mohmmed, Shams Kareem; Auda, Shaimaa Awadh; Jasim, Haider Mahmod (American Journal of Bioscience and Clinical Integrity, 2026)
Medicinal plants have gained an important source in traditional medicine, and drug production in various countries of the world. A percentage 80% of the world’s population depends on them due to their availability, ease of access, and low cost. Hence, the importance of our study emerged, which dealt with the effect of the extract of the white Artemisia herba-alba plant, which is widespread in the desert of Al-Muthanna Governorate, on the microorganisms isolated from patient with gingivitis. A moleculer docking simulation was also carried out for the flavonoids that are abundant in the Artemisia herba-alba extract. In the laboratory, agar diffusion experiments were conducted to assess the inhibitory effects of Artemisia herba-alba extract and some selected antibiotics on bacterial growth. while the in-silico approach involved consensus sequence and structural analyses of topoisomerase and DNA gyrase through docking and molecular-dynamics simulation. The results revealed that Artemisia herba-alba extracts, particularly flavonoids, displayed significant antimicrobial activity against all types of bacteria (P ≤ 0.05). Artemisia herba-alba extract exhibited the most potent effects, while ciprofloxacin showed comparatively lower activity. Docking analysis demonstrated strong interactions between the inhibitors and topoisomerase and DNA gyrase, with the inhibitors binding within the domain regions. These findings underscore the promising antimicrobial properties of Artemisia herba-alba extracts, with flavonoids being particularly effective against antibiotic-resistant bacteria. Continued research in this domain holds the potential for developing novel and effective antimicrobial agents based on Artemisia herba-alba, thereby potentially reducing reliance on conventional antibiotics.